Effect of γ Irradiation on Germination of Rice (Oryza Sativa L.) - Chaturvedi, Anurag; Sreedhar, M.; Singhal, R. K.; Venubabu, P.; Kumar, D. Pavan; Aparna, M. (International Journal of Bio-resource and Stress Management, 2023)
The present investigation aimed at estimating the influence of γ rays, confirmed suppressive effect on germination and seedling parameters of rice compared to non-irradiated seed. Seeds of paddy (BPT 5204) were exposed to different doses of γ rays ranging from 0.40 KGy to 2.00 KGy using Co60 γ radiation (GC 5000) facility at Quality Control Laboratory, Acharya N. G. Ranga Agricultural University, Rajendranagar, Hyderabad during 2010-11. The experimental results revealed that the percentage of germination decreased after irradiation and the effect became stronger with increase of γ dose. Parameters such as germination percentage, speed of germination, mean daily germination, peak value and germination value have significantly decreased with increased irradiation doses. Similarly, seedling parameters, viz. shoot length, root length and vigor index and root and shoot length ratio expressed higher reduction at higher doses as compared to untreated control. The study clearly indicated the deleterious effects of γ irradiation increased at regular intervals, with attainment of LD50 at a dose of 1.20 KGy.